Effectiveness of Nanocatalyst in the Improvement of Sorghum Bagasse Particleboard Bonded with Bio-Adhesive - Yunia Frida Adelka; Deni Purnomo; Sudarmanto; Narto; Bernadeta Ayu Widyaningrum; Murni Handayani; Jajang Sutiawan; Kenji Umemura; Dede Hermawan; Sukma Surya Kusumah (Jurnal Sylva Lestari, 2023)
Modification in the manufacturing process of bio-adhesive need to be carried out to improve the properties of sorghum bagasse particleboard, such as adding nanocatalyst into the bio-based adhesive. This study was conducted to determine the effectiveness of nanocatalyst in enhancing the properties of sorghum bagasse particleboard. Each nanocatalyst, such as zinc oxide (ZnO) and graphene oxide (GO), has been added to the citric acid and molasses-based adhesives. The target density of the particleboard was 0.8 g/cm3, with a board size of 350 mm × 350 mm × 6 mm. The particleboard was pressed using a hot-pressing machine at a temperature of 200°C and 10 MPa of pressure for 10 min. The physical and mechanical properties of the particleboard were evaluated, referring to JIS A 5908:2022 standard. The result showed that adding GO into the citric acid-based adhesive obtained a higher modulus of rupture (MOR) and lower thickness swelling (TS) than the others. Consequently, adding GO is more effective than adding ZnO into the bio-based adhesive in enhancing the properties of the particleboard. Keywords: bagasse sorghum, citric acid, molasses, Nanocatalyst GO, Nanocatalyst ZnO